Assessment of Short-Term Patient Outcomes Following Overlapping Orthopaedic Surgery at a Large Academic Medical Center. (15th April 2020) - Glauser, Gregory; Osiemo, Benjamin; Goodrich, Stephen; McClintock, Scott D.; Weber, Kristy L.; Levin, L. Scott; Malhotra, Neil R.
Abstract : Background: Overlapping surgery is a long-standing practice that has not been well studied. The aim of this study was to assess whether overlapping surgery is associated with untoward outcomes for orthopaedic patients. Methods: Coarsened exact matching was used to assess the impact of overlap on outcomes among elective orthopaedic surgical interventions (n = 18, 316) over 2 years (2014 and 2015) at 1 health-care system. Overlap was categorized as any overlap, and subcategories of exclusively beginning overlap and exclusively end overlap. Study subjects were matched on the Charlson comorbidity index score, duration of surgery, surgical costs, body mass index, length of stay, payer, and race, among others. Serious unanticipated events were studied. Results: A total of 3, 395 patients had any overlap and were matched (a match rate of 90.8% of 3, 738). For beginning and end overlap, matched groups were created, with a match rate of 95.2% of 1043 and 94.7% of 863, respectively. Among matched patients, any overlap did not predict an unanticipated return to surgery at 30 days (8.2% for any overlap and 8.3% for no overlap; p = 0.922) or 90 days (14.1% and 14.1%, respectively; p = 1.000). Patients who had surgery with any overlap demonstrated no difference compared with controls with respect to reoperation, readmission, or emergency room (ER) visits at 30 or 90 days (a reoperation rate of 3.1% and 3.2%, respectively [p = 0.884] at 30 days and 4.2% and 3.5% [p = 0.173] at 90 days; a readmission rate of 10.3% and 11.0% [p = 0.352] at 30 days and 5.5% and 5.2% [p = 0.570] at 90 days; and an ER visit rate of 5.2% and 4.6% [p = 0.276] at 30 days and 4.8% and 4.3% [p = 0.304] at 90 days). Patients with surgical overlap showed reduced mortality compared with controls during follow-up (1.8% and 2.6%, respectively; p = 0.029). Patients with beginning and/or end overlap had a similar lack of association with serious unanticipated events; however, patients with end overlap showed an increased unexpected rate of return to the operating room after reoperation at 90 days (13.3% versus 9.7%; p = 0.015). Conclusions: Nonconcurrent overlapping surgery was not associated with adverse outcomes in a large, matched orthopaedic surgery population across 1 academic health system. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.